The Role of Students Parent in Shaping Home Learning Environment (HLE) for Early Childhood - Pramesti Indah Kumalasari; Sugito Sugito (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to determine the role of parents in forming a Home Learning Environment (HLE) for early childhood in Trucuk, Klaten. This study used a qualitative approach with descriptive methods and was carried out by purposive sampling. The research subjects were 5 parents who have children aged 3-4 years. Data collection techniques used were observation, interviews, and documentation techniques. Data analysis used was data collection, data reduction, data presentation, and drawing conclusions. Based on the research that has been done, the role of parents in shaping HLE is seen when parents introduce new learning materials into the home through activities (playing, chatting and reading), preparing HLE according to children's needs and interests, offering various learning opportunities and providing learning experiences that are fun. With the role of parents in shaping HLE, it can be an early intervention program and direct children's activities to be more useful in reaching the next stage of development.